Governor Rate-Constrained Opf for Primary Frequency Control Adequacy - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2014)
The integration of non-dispatchable generation has led to a change in the dynamics of primary frequency response. This change, mostly driven by the limited contribution of non-dispatchable generation to both total system inertia and governor response, may deteriorate the performance of current practices for determining primary reserves to the extend that real time operation reliability may no longer be ensured. This work establishes sufficient conditions for ensuring primary response adequacy through ex-ante dispatch instructions. A simplified dynamic model of primary frequency response (including system inertia, system governors ramp rates, and dead bands) is developed to formulate a constraint suitable for an OPF framework. A simulation of ERCOT is presented to test the proposed formulation. © 2014 IEEE.